Exploratory evaluation of immunotherapy response and medication use in endometrial and cervical carcinoma - Julia Chalif; Molly Morton; Eric McLaughlin; Anna Gonzalez; Jessica Fulton; Jessica Sciuva; Ioana Marcu; Kristin L. Bixel; David E. Cohn; Casey M. Cosgrove; Larry J. Copeland; Christa I. Nagel; et al. (Gynecologic Oncology Reports)
Objective: (s): To assess the effect of medication use during immune checkpoint inhibitor (ICI) therapy on treatment response and oncologic outcomes. Methods: An IRB-approved single-institution retrospective cohort study was performed in patients with endometrial cancer (EC) and cervical cancer (CC) who were treated with ICIs from January 1, 2017 to January 1, 2023. Concomitant medications used during the ICI course were recorded. The associations between medication use and ICI response, progression-free survival (PFS), and overall survival (OS) was assessed. Results: 217 CC and EC patients were treated with ICIs during this study period; 32 % (n = 71) had CC, and 67 % (n = 146) had EC. There was a significant difference in ICI complete response between CC patients who did and did not use oral steroids during treatment. Of CC patients who achieved a complete response, 28 % (n = 7) used steroids vs. 13.6 % (n = 6) of non-steroid users (Fisher’s exact p = 0.045). In patients with EC, proton pump inhibitor (PPI) use was associated with ICI response, with 43.8 % (n = 21) of PPI users achieving a complete response vs. 16.3 % (n = 15) of non-PPI users (chi-squared p = 0.002). PPI use in the EC cohort was associated with improved progression-free survival and overall survival (log-rank p < 0.05). This was also demonstrated among mismatch repair-deficient EC patients where PPI use during ICI therapy significantly associated with both PFS (HR 0.26, 95 % CI 0.12–0.55; p < 0.001) and OS (HR 0.22, 95 % CI 0.08–0.59; p < 0.001).Conclusion(s)In this retrospective cohort study of EC and CC patients treated with ICI therapy, medication use, specifically PPIs and oral steroids, was seen to have a significant positive effect on ICI response, PFS, and OS.